2019
DOI: 10.3390/ijms20040794
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, Autonomic Nervous Function and Atherosclerosis

Abstract: Behavioral and psychosocial factors related to development of cardiovascular disease have been gaining increased attention. Notably, sleep is considered to be one of the most important behavioral factors involved in progression of atherosclerosis and cardiovascular events, with autonomic nervous function a potential mechanism. Several studies have shown associations of sleep and autonomic dysfunction with major surrogate markers of atherosclerosis, such as carotid intima-media thickness and arterial stiffness.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 87 publications
1
22
0
2
Order By: Relevance
“…26 There is also some evidence linking sleep duration with cardiac arrhythmias. 32 Oxidative stress, systemic inflammation, and autonomic and endothelial dysfunction can play role. 27 It may be reasonable to hypothesize that habitual long sleep can reset the circadian pacemaker into a chrono-biological state, and neuro-cardio-electrophysiological excitability can alter conduction of cardiac impulses and predispose to alterations in hearth rhythm.…”
Section: S Leep Dur Ati On and S Trok E Ris Kmentioning
confidence: 99%
See 4 more Smart Citations
“…26 There is also some evidence linking sleep duration with cardiac arrhythmias. 32 Oxidative stress, systemic inflammation, and autonomic and endothelial dysfunction can play role. 27 It may be reasonable to hypothesize that habitual long sleep can reset the circadian pacemaker into a chrono-biological state, and neuro-cardio-electrophysiological excitability can alter conduction of cardiac impulses and predispose to alterations in hearth rhythm.…”
Section: S Leep Dur Ati On and S Trok E Ris Kmentioning
confidence: 99%
“…In the Physicians' Health Study, prolonged sleep time exceeding 8 hours was related to atrial fibrillation (AF). 32 In animal models, chronic sleep fragmentation was found to determine morphological changes of vessels, characterized by derangement of elastic fibers and recruitment of inflammatory cells. 28 Other studies provided indirect evidence of the potential relationship between sleep and AF: prolonged P-wave duration and P-wave dispersion and higher risk of atrial electro-mechanical delay have been reported in sleep deprived adults.…”
Section: S Leep Dur Ati On and S Trok E Ris Kmentioning
confidence: 99%
See 3 more Smart Citations